Do External Knowledge Spillovers Induce Firms'Innovations? Evidence from Slovenia - Jože P. Damijan; Andreja Jaklic; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
The paper analyses whether, and to what extent, firm's ability to innovate is induced by firm's own R&D activity and to what extent by factors external to firm. It first estimates the impact of firms' internal R&D capital and external R&D spillovers on firms' innovation activity within an integrated dynamic model. In the second step, we then estimate the impact of firms'innovations on firms?productivity growth. Using the firm level data on innovation activity combined with firms' financial data for a large sample of Slovenian firms in the period 1996-2002, the paper produces three main findings. First, firm's own R&D expenditures as well as external knowledge spillovers, such as national and international public R&D subsidies, foreign ownership and intra-sector innovation spillovers do enhance firm's ability to innovate. Second, innovations as a result of firm's R&D do contribute substantially to firm's total factor productivity growth. And third, foreign ownership has a double impact on firm's TFP growth - it first enhances firm's ability to innovate and then it additionally contributes to firm's TFP growth via superior organization techniques and other channels of knowledge diffusion.
Keywords: D24; F14; F21; 330; innovation; external knowledge spillovers; FDI; Slovenia; Innovation; Produktivität; Betriebliche Forschung; Direktinvestition; Externer Effekt; Wissenstransfer; Schätzung; Slowenien